Children’s Emotional Well-being in Family and Educational Contexts: A Qualitative Study with Parents, Children, and Professionals in Spain - Santaolalla, Pablo; Gonzálvez, María T.; Espada, José P.; Orgilés, Mireia; Morales, Alexandra (Child Indicators Research, 2026)
Children’s emotional well-being is shaped by family routines, relational dynamics, and everyday stressors. While mental health in childhood is gaining increased attention, little is known about how children and their caregivers make sense of emotional well-being in daily life. This study explores the perspectives of children (aged 8 to 11), their parents, and professionals working in education and psychology. A total of nine focus groups (N = 58) were conducted across three Spanish autonomous communities located in the east, southeast, and south of the country, using a semi-structured script focused on routines, stress management, social pressure, family organization, and perceived support needs. Thematic analysis revealed that children associate emotional well-being with feeling safe, being heard, and having time for rest and play. Parents emphasized challenges related to time constraints, digital saturation, and emotional connection. Professionals highlighted systemic issues, including overstimulation, the absence of emotional education, and a lack of coordination between institutions. Despite their distinct perspectives, all groups consistently emphasized the importance of emotion regulation, caring relationships, and accessible support. The findings highlight the need for multi-level strategies that promote emotional well-being through both relational care and coordinated systemic interventions. By centering on lived experiences, this study offers valuable insights to guide the development of preventive strategies that are closely aligned with children’s everyday realities. The findings support the design of contextually grounded and developmentally appropriate interventions with potential implications for both mental health policy and educational practice.
Keywords: emotional well-being; children; parenting; professional support; qualitative research